Application of the Certainty Factor Method for Mobile-Based Identification of Freshwater Fish Diseases - Santoso, Heri; Suhardi, Suhardi; Ridho Pardomuan, Mohammad (PT Mattawang Mediatama Solution, 2023)
Freshwater fish its the food sources with profitable sales, consistent care can achieve the maintenance process until successful. Freshwater fish that have a high selling value include Gurami and Catfish. Gurami fish sales per seedling Rp. 3,000 and Lele fish sales start from Rp. 1000 to Rp. 0.500. Fish care needs to be considered to maintain its quality. Various problems are also experienced by farmers. The slow identification process makes fish affected by the disease faster and loses. Several factors inhibit the fish is of illegal drugs, overfeed, and environmental unhygiene conditions. The role of experts that is not sufficiently available makes limited information about controlling fish diseases so that it takes time and costs little. Utilizing technological progress, expert systems can help to solve problems that previously could only be solved by an expert. The Forward Chaining Method is a method on an expert system that is able to do a reasoning with advanced forward techniques. The Certainty Factor method is a method that can give a degree of confidence in a disease. An expert system built to identify freshwater fish diseases was built into the deep android operating system by the Waterfall development method. Data taken includes as many as 10 symptom data and 29 disease data implemented into the system. With this expert system in place, it aims to provide benefits to facilitate access in adding information about fish diseases so that countermeasures become faster